2023
DOI: 10.1097/aog.0000000000005269
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Pregnant Individuals

Abstract: SUMMARY Urinary tract infection (UTI) is one of the more common perinatal complications, affecting approximately 8% of pregnancies (1, 2). These infections represent a spectrum, from asymptomatic bacteriuria, to symptomatic acute cystitis, to the most serious, pyelonephritis. The presence of UTIs has been associated with adverse pregnancy outcomes, including increased rates of preterm delivery and low birth weight. Screening for and treating asymptomatic bacteriuria have been shown in multiple studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The use of fluoroquinolones and trimethoprim-sulfamethoxazole is generally discouraged in pregnancy [30]. The guideline endorsed by the American College of Obstetricians and Gynecologists should be considered for treatment approach in this particular patient population [31]. Lastly, the proposed recommendations presented are for the clinical diagnosis of APN only, and are not appropriate for the management of UTIs with complicating factors such as urinary tract obstruction.…”
Section: Limitationsmentioning
confidence: 99%
“…The use of fluoroquinolones and trimethoprim-sulfamethoxazole is generally discouraged in pregnancy [30]. The guideline endorsed by the American College of Obstetricians and Gynecologists should be considered for treatment approach in this particular patient population [31]. Lastly, the proposed recommendations presented are for the clinical diagnosis of APN only, and are not appropriate for the management of UTIs with complicating factors such as urinary tract obstruction.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies have shown that women with a UTI, particularly those requiring an emergency department visit or hospitalization, face an increased risk of preterm and early term births [ 4 , 5 ]. This is a critical concern, as UTIs are one of the more common perinatal complications, affecting approximately 8% of pregnancies and representing a spectrum from asymptomatic bacteriuria to more severe infections like pyelonephritis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%